2007
DOI: 10.1158/0008-5472.can-06-2968
|View full text |Cite
|
Sign up to set email alerts
|

Gene and Protein Expression Profiling of Human Ovarian Cancer Cells Treated with the Heat Shock Protein 90 Inhibitor 17-Allylamino-17-Demethoxygeldanamycin

Abstract: The promising antitumor activity of 17-allylamino-17-demethoxygeldanamycin (17AAG) results from inhibition of the molecular chaperone heat shock protein 90 (HSP90) and subsequent degradation of multiple oncogenic client proteins. Gene expression microarray and proteomic analysis were used to profile molecular changes in the A2780 human ovarian cancer cell line treated with 17AAG. Comparison of results with an inactive analogue and an alternative HSP90 inhibitor radicicol indicated that increased expression of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
129
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(145 citation statements)
references
References 55 publications
16
129
0
Order By: Relevance
“…8 In this study, we were unable to detect any alteration in genes coding for known Hsp90 client proteins including c-Raf-1, ErbB2, Akt, and cyclin-dependent kinase 4. Similarly, other investigators have found these phenomena in other cancer types (18,19). Interestingly, when we compared our results with a recently published study in ovarian cancer, we found that only the 70 kDa heat shock protein isoforms and eukaryotic translation initiation factor 3 matched between these two tumor types.…”
Section: Discussionsupporting
confidence: 84%
“…8 In this study, we were unable to detect any alteration in genes coding for known Hsp90 client proteins including c-Raf-1, ErbB2, Akt, and cyclin-dependent kinase 4. Similarly, other investigators have found these phenomena in other cancer types (18,19). Interestingly, when we compared our results with a recently published study in ovarian cancer, we found that only the 70 kDa heat shock protein isoforms and eukaryotic translation initiation factor 3 matched between these two tumor types.…”
Section: Discussionsupporting
confidence: 84%
“…HSP27 was also induced after treatment with VER-49009 and VER-50589. We previously reported up-regulation of HSP27 in other cell lines and also in tumor tissues obtained from patients receiving 17-AAG in a phase I clinical trial at our institution (52). Both HSP72 and HSP27 have cytoprotective roles (49), and the induction of these chaperones and stress proteins may reduce the apoptotic response to HSP90 inhibitors.…”
Section: Discussionmentioning
confidence: 84%
“…Using proteomic analysis, we discovered that expression of the protein arginine methyltransferase PRMT5 was decreased by 17-AAG in human cancer cell lines (52). PRMT5 was shown to be a novel HSP90-binding partner and potential client protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 17-AAG decreases a group of Myc-regulated mRNAs and increases the mRNA expression of Hsp90b, Hsp72, Hsp70, Hsp47 and Hsp27. 39 The major molecular chaperones Hsp90, Hsp70 and Hsp60 interact with newly synthesized polypeptides, and maintain the proteins in unfolded states that are suitable for translocation across the membrane. The nuclear translocation of heparanase is abolished by GA and 17-AAG in HL-60 cells, indicating that Hsp90 is involved in the nuclear translocation of heparanase.…”
Section: Hsp90 Inhibitors Are Promising For Cancer Therapymentioning
confidence: 99%